Stylolites and stylolite networks as primary controls on the geometry and distribution of carbonate diagenetic alterations - Gomez-Rivas, Enrique; Martin-Martin, Juan Diego; Bons, Paul D.; Köhn, Daniel; Griera, Albert; Trave, Anna; Llorens, Maria-Gema; Humphrey, Elliot; Neilson, Joyce (Marine and Petroleum Geology, 2022)
There is ongoing debate on whether stylolites act as barriers, conduits, or play no role in fluid transport. This problem can be tackled by examining the spatial and temporal relationships between stylolites and other diagenetic products at multiple scales. Using the well-known Lower Cretaceous Benic`assim case study area (Maestrat Basin, E. Spain), we provide new field and petrographic observations of how bedding-parallel stylolites can influence different diagenetic processes during basin evolution. The results reveal that stylolites can serve as baffles or inhibitors for different carbonate diagenetic reactions, and act as fronts for dolomitization, dolomite recrystallization and dolomite calcitization processes. Anastomosing stylolites that pre-date burial dolomitization probably acted as a collective baffle for dolomitization fluids in the study area, resulting in stratabound replacement geometries at the metre-to-kilometre scale. The dolomitization front coincides with stylolites, and can be traced along consecutive anastomosing ones. Such anastomosing stylolites are typical of mud-dominated facies that characterize limestone-dolostone transition zones. Conversely, dolostone bodies tend to correspond to more grain-dominated facies characterized by parallel (non-anastomosing) stylolites. Stylolites subsequently acted as fluid flow conduits and barriers when the burial and stress conditions changed. Stylolitic porosity enhanced by dissolution within dolostones close to faults appears filled with saddle dolomite riming the stylolite pore, and high-temperature blocky calcite cements filling the remaining porosity. The fluids responsible for these reactions were likely released from below at high pressure, causing hydraulic brecciation, and were channelised through stylolites, which acted as fluid conduits. Stylolites are also found acting as baffles for subsequent dolomite calcitization reactions during meteoric diagenesis and occasionally appear filled with iron oxides likely released by calcitization. This example demonstrates how the same type of stylolites (bedding-parallel) can act as barriers/inhibitors and/or conduits for different types of diagenetic reactions through time, and how important it is to consider their collective role when they form networks.
CRIS-Team WoS Importer:2022-02-11